A expansão do curso de Direito no estado de Mato Grosso : 2001-2011 - Balbo, Gisele Cristina (2014)
This paper discusses the theme of " the expansion of the law school in the state of Mato Grosso : 2001-2011 ." From this perspective, seeks to understand the economic, political and social elements that pervade the history of the law school at the national and state levels. As a general purpose research examines the expansion of law school in the state of Mato Grosso, emphasizing the link with the politics of higher education in the country. This is a survey that seeks Marxist theoretical contribution in its reasoning. Alongside this approach, discusses the expansion of the law school and its meanings. The research presents quantitative data on the area of law in relation to courses and places, based on the Census of Higher Education, in delimited period; also collects data ENADE / MEC to situate the evaluation of courses of law in the state of Mato Grosso. Also features interviews with representatives of legal education through a public and a private institution, as well as the Bar Association Section Mato Grosso. With them, sought to discuss and understand the consequence of the expansion stroke. The research shows that the expansion of the law school in the state of Mato Grosso stood in greater proportion in private institutions (college) and within the state. In turn , the note ENADE, which aims to assess the performance of students graduating from law school shows that the public higher education institutions the concept considered high ( grade 4 and 5) is predominant and in private institutions predominant concept 2 . Examination in order it was found that enrollees had lower utilization, thus reducing the insertion of new professionals in the labor market to work in advocacy. Then, it concludes that the expansion of the law school in the state of Mato Grosso , in the period 2001-2011 , relates to the policies of expansion of higher education in the country in the following aspects : the expansion occurs in the private sector and in non- university institutions.